A proposed social network analysis platform for big data analytics - Chang, Victor (Technological forecasting & social change, 2018)
This paper presents an important concept of Internet of People, a social network analysis approach to perform Big Data Analytics. The paper describes the development, management implications and analysis. To illustrate six points in the management issues, an in-house development of a SocialNetwork API with six functions has been demonstrated. The proposed method is focused on processing the contacts who click like or comment on the author's posts, as well as the queries and visualization. Results can be extracted and presented in data visualization. Six functions in the SocialNetwork API have evaluation tests, including a large scale of 50,000simulations completed within 60,000s. Results support our case of Big Data processing for social network analysis can be equivalent to CRM, ERP and MIS. Additionally, there are no costs involved. Related topics have been discussed in details. Our research contributions have been consolidated since our work have met research challenges for social network analysis and six management implications. •We identify six management issues for social networks and justify our contributions.•We have developed SocialNetwork API to extract and process data from Facebook.•Outputs of our analysis are in analytics with six different functions.•SocialNetwork API was tested thoroughly to confirm its resiliency.•We justified our research contributions for Big Data Analytics by SocialNetwork API.